Experimentally quantifying critical stresses associated with basal slip and twinning in magnesium using micropillars. (15th August 2017) - Liu, Y.; Li, N.; Arul Kumar, M.; Pathak, S.; Wang, J.; McCabe, R.J.; Mara, N.A.; Tomé, C.N.
Abstract: Basal slip and { 01 1 ¯ 2 } twinning are two major plastic deformation mechanisms in hexagonal closed-packed magnesium. Here we quantify the critical stresses associated with basal slip and twinning in single-crystal and bi-crystal magnesium samples by performing in situ compression of micropillars with different diameters in a scanning electron microscope. The micropillars are designed to favor either slip or twinning under uniaxial compression. Compression tests imply a negligible size effect related to basal slip and twinning as pillar diameter is greater than 10 μm. The critical resolved shear stresses are deduced to be 29 MPa for twinning and 6 MPa for basal slip from a series of micropillar compression tests. Employing full-field elasto-visco-plastic simulations, we further interpret the experimental observations in terms of the local stress distribution associated with multiple twinning, twin nucleation, and twin growth. Our simulation results suggest that the twinning features being studied should not be close to the top surface of the micropillar because of local stress perturbations induced by the hard indenter. Graphical abstract: Image 1